Pengembangan Pengembangan Sistem Monitoring Kelembapan dan Suhu pada Penyimpanan Gudang Loofah dengan Penggunaan Humidifier - Bani, Fajar Ciputra; Matalata, Hijir; Adam Firmansyah, Aulia; Dipo Afriza, Dwiki; Nanda Putri, Lutfiah (Journal of Energy, Materials, & Manufacturing Technology, 2024)
This study aims to develop a humidity and temperature monitoring system for loofah warehouse storage using a humidifier to maintain storage environment stability. The research method includes needs analysis, system design, implementation, and testing. The system design includes temperature and humidity sensors connected to an Arduino microcontroller, which controls the humidifier to maintain temperature and humidity within the desired range. Testing was conducted under warehouse simulation conditions with temperature and humidity variations, as well as in actual loofah warehouses. The research findings indicate that the developed monitoring system is capable of maintaining temperature and humidity levels within the loofah warehouse at the desired level. Implementing this system can help optimize loofah storage conditions, reduce product damage, and improve storage efficiency.